The Cambridge aerospace dictionary - Gunston, Bill (Cambridge University Press, 2009)
The Cambridge Aerospace Dictionary is scholarly, accessible, and essential reading for those interested in flight and the aerospace industry.
Keywords: Aerospace engineering -- Dictionaries.; Aeronautics -- Dictionaries.; Astronautics -- Dictionaries.; elektronické knihy; electronic books